The Effect of Fermented Sauropus androgynus Plus Bay Leaf Inclusion on the Hematologic and Lipid Profiles of Female Broiler Chickens - Santoso , Urip; Fenita, Yosi; Kususiyah (International Journal of Poultry Science, 2018)
Background and Objective: The use of antibiotics as a feed additive for poultry has been prohibited in many countries because the antibiotics accumulate in the meat, which may stimulate microbial pathogen resistance. The present study was conducted to evaluate the effect of fermented Sauropus androgynus plus bay leaf inclusion on the hematologic and lipid profiles of female broiler chickens. Materials and Methods: Two hundred and eighty female broilers aged 14 days were divided into 7 treatment groups as follows: 1) the control broiler chickens were fed a diet with a commercial feed additive (contained zinc bacitracin) (P0), 2) broiler chickens were fed a diet with medicinal herb mixture formula 1 at 2.5% (P1), 3) broiler chickens were fed a diet with medicinal herb mixture formula 2 at 2.5% (P2), 4) broiler chickens were fed a diet with medicinal herb mixture formula 3 at 2.5% (P3), 5) broiler chickens were fed a diet with medicinal herb mixture formula 1 at 5% (P4), 6) broilers were fed a diet with medicinal herb mixture formula 2 at 5% (P5) and 7) broilers were fed a diet with medicinal herb mixture formula 3 at 5%. Results: Experimental results showed that the inclusion of fermented Sauropus androgynus plus bay leaves had no effect on thrombocyte levels, erythrocyte sedimentation rate (ESR), WBC, RBC, PCV, MCV, MCH, MCHC, liver and spleen weights, intestine length and toxicity but significantly affected the gizzard; the intestine (p<0.01) and heart weights (p<0.05); triglyceride, cholesterol, HDL (p<0.01) LDL and VLDL (p<0.05) levels; and the LDL/HDL ratio (p<0.01). Conclusion: The inclusion of fermented Sauropus androgynus plus bay leaves improved the lipid profile without modifying the hematologic status in female broiler chickens.